Chinese Medicine - Wang, Yi-tao; Wang, Chunming
Chinese Medicine is an open access journal publishing evidence-based, scientifically justified research and review papers in all aspects of Chinese medicine, including - but not limited to - chemistry, biology, pharmacology, pharmaceutics, engineering, clinical applications and socioeconomics that are relevant and significant to Chinese medicine. We particularly welcome studies using interdisciplinary methods and technologies to: - discover new compounds from Chinese medicinal herbs - elucidate molecular/cellular targets and mechanisms of action for Chinese medicine - develop modern drug delivery and molecular pharmaceutic tools for Chinese medicine - evaluate the outcomes of hypothesis-driven, rationally-designed fundamental, pre-clinical and clinical research We now publish research and review papers, both unsolicited and solicited. We may publish opinion or commentary papers which are by invitation only. Normally, we do not publish such types of papers as case study, technical note or meta-analysis unless the topic is of exceptionally significance and urgency.